An integrated DRASTIC model using frequency ratio and two new hybrid methods for groundwater vulnerability assessment - Neshat, Aminreza; Pradhan, Biswajeet (Springer, 2015)
Groundwater management can be effectively implemented by mapping groundwater contamination. Intense agricultural activities and land overexploitation have resulted in groundwater contamination, which is becoming a critical issue, specifically in areas where fertilizers are extensively used on large plantations. The goal of this study was to develop an integrated DRASTIC model with a frequency ratio (FR) as a novel approach. Two new hybrid methods namely single-parameter sensitivity analysis (SPSA) and an analytical hierarchy process (AHP) are also implemented for adjusting feature weights to local settings. The FR is used for DRASTIC model rates, whereas both SPSA and AHP are used for DRASTIC weights. The FR-DRASTIC, FR-SPSA and FR-AHP methods are developed; nitrate samples from the same month in different years are used for analysis and correlation (May 2010 and May 2012). The first nitrate samples are interpolated using the Kriging approach. The Kerman plain is used as an example, which is located in south-eastern part of Iran. Additionally, the new methods are employed in the study area to compare with each other and the original DRASTIC model. The validation results exhibited that using FR approach improved the correlation between vulnerability index and nitrate concentrations compared with original DRASTIC vulnerability correlation which was 0.37. The results indicated that the new hybrid methods exhibited higher correlation 0.75 in the FR-DRASTIC model. Correlations of the FR-SPSA and FR-AHP approaches were 0.77 and 0.80. Hence, the new hybrid methods are more effective and provide reasonably good results. Furthermore, quantitative measures of vulnerability offer an excellent opportunity to effectively prevent as well as reduce contamination.